Implementasi Supervisi Pendidikan Berbasis Digital di Era Transformasi Teknologi Sekolah - Zulfa Telian Ristamala; Siti Khulasoh (Hayati : Jurnal Pendidikan, 2026)
The development of digital technology has transformed educational supervision practices in schools, particularly in the collection of learning materials, classroom observations, and communication between teachers and principals. This study aims to analyze the implementation of digital-based educational supervision, the challenges faced, and its impact on improving teacher professionalism. This study employed a literature review method with a qualitative descriptive approach, reviewing 10 national scientific articles published between 2020 and 2023 and relevant supporting documents. Data analysis was conducted using content analysis techniques to identify key patterns and findings related to the implementation of digital supervision. The results indicate that digital supervision can simplify the documentation process, accelerate communication, and provide a more focused space for teacher reflection. Teachers become more thorough and structured in preparing learning materials, while principals can provide more targeted feedback. However, the effectiveness of digital supervision is influenced by teachers' digital literacy, principal support, and the availability of facilities and infrastructure. If these factors are met, digital-based supervision can run optimally and contribute to improving the quality of learning, teacher professionalism, and a more accountable work culture in schools. Keywords: Educational Supervision, Digital Supervision, Teacher Professionalism, Work Culture, Technology-Based Education